Porphyry Cu fertility of the Loch Lilly-Kars Belt, Western New South Wales, Australia. Issue 1 (2nd January 2020) - Baatar, B.; Parra-Avila, L. A.; Fiorentini, M. L.; Polito, P.; Crawford, A. J.
Abstract: This study investigates the prospectivity for porphyry Cu mineralisation of the early Paleozoic Loch Lilly-Kars Belt, which follows the southern margin of the Paleoproterozoic Broken Hill (Willyama) Inlier in western New South Wales, Australia. The belt is thought to have resulted from the 515–510 Ma collision of a volcanic passive margin and an intra-oceanic island arc above a west-dipping subduction zone, with subsequent post-collisional magmatism. To identify fertility signals of selected magmatic intrusive rocks, we combined whole-rock analyses with in-situ zircon trace-element and isotopic measurements. Data reveal that both Cambrian ( ca 496 Ma) and Devonian ( ca 393 Ma) intrusive suites are present in the Loch Lilly-Kars Belt. Cambrian dioritic rocks are largely non-fertile for porphyry Cu mineralisation, whereas Devonian monzodiorites and monzonitic porphyries carry strong fertility signals that include high whole-rock Sr/Y (>35) and V/Sc (>10) values, associated with the occurrence of equant, stubby zircons showing relatively constant Eu/Eu* values without any significant Eu anomalies. Although only few samples were analysed and more intensive exploration is required, the results of this study indicate significant potential for porphyry Cu mineralisation in this poorly known belt.